Personality and lifestyle interprets external condition to environmental behaviours - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Hitam, Mizan (Malaysian Institute Of Planners, 2020)
Personality and lifestyles frame individuals’ interpretation of situational information; as such, the encouragement, convenience and reinforcement to behave more environmentally. Issue: Existing research lack empirical evidence on the influence of personality and lifestyle (PL) on external condition (EC) to environmental behaviours. Purpose: This paper aims to verify the statistical predictability of EC based on PL. Approach: Multiple Correlation and Multiple Linear Regression were carried out to assess linear associations and parameters of linear equations to predict EC components based on PL items. Findings: EC components were predictable by some of the PL items. In particular, ‘urging media to raise environmental awareness’ was the strongest predictor of EC.